2022
DOI: 10.1007/s00436-022-07562-z
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary review about Encephalitozoon cuniculi in a One Health perspective

Abstract: Encephalitozoon cuniculi is a microsporidian parasite mostly associated with its natural host, the rabbit ( Oryctolagus cuniculus ). However, other animals can be infected, like other mammals, birds, and even humans. Although it usually causes subclinical infection, it can also lead to encephalitozoonosis, a clinical disease characterized by neurological, ocular, and/or renal signs that can be even fatal, especially in immunocompromised individuals. Therefore, this multidiscip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 122 publications
(320 reference statements)
1
11
0
1
Order By: Relevance
“…This is a microsporidian parasite associated with its natural host ( Oryctolagus cuniculus ) and has a broad range of hosts, with zoonotic potential, inducing neurologic, ocular and renal clinical signs. The parasite is responsible for clinical forms in blue and silver foxes [ 63 ]. Red foxes are reported to be infected in Ireland with about 0.7% prevalence [ 64 ], in Czech Republic with 3.8% [ 61 ], while in a further study in the same area microsporidian DNA was not detected [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a microsporidian parasite associated with its natural host ( Oryctolagus cuniculus ) and has a broad range of hosts, with zoonotic potential, inducing neurologic, ocular and renal clinical signs. The parasite is responsible for clinical forms in blue and silver foxes [ 63 ]. Red foxes are reported to be infected in Ireland with about 0.7% prevalence [ 64 ], in Czech Republic with 3.8% [ 61 ], while in a further study in the same area microsporidian DNA was not detected [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence rates (Hublin et al, 2021;Shams et al, 2021) and concomitant infections by several Blastocystis subtypes have been reported globally in cattle (Abarca et al, 2021;Maloney, Lombard, et al, 2019) Leporids including rabbits and hares are recognized as suitable hosts for microsporidial pathogens, particularly E. cuniculi and, to a lesser extent, E. bieneusi (Mathis et al, 2005;Wasson & Peper, 2000). Although E. cuniculi usually causes subclinical infection in humans, it can also lead to encephalitozoonosis, a clinical disease characterized by neurological, ocular and/or renal signs that can be even fatal, especially in immunocompromised individuals (Dipineto et al, 2008;Künzel et al, 2008;Magalhães et al, 2022;Valencakova et al, 2008). In a seminal Spanish study, E. bieneusi was described for the first time in wild rabbits (del Aguila et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…2 E. cuniculi is a zoonotic microsporidian parasite with a wide host range, for which the rabbit is the natural host. 3 Assessment of healthy pet rabbits in the UK suggests that there may be relatively wide exposure to E. cuniculi, with 23%-52% of animals being seropositive, depending on the study. 4,5 Rabbits with encephalitozoonosis may be presented with severe renal disease secondary to infection with the organism, but chronic renal lesions comprising inflammatory foci focused on tubular epithelial cells, together with renal fibrosis causing macroscopically pitted kidneys, may also be detected at postmortem examination in the absence of a preceding diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…E. cuniculi is a zoonotic microsporidian parasite with a wide host range, for which the rabbit is the natural host 3 . Assessment of healthy pet rabbits in the UK suggests that there may be relatively wide exposure to E. cuniculi , with 23%–52% of animals being seropositive, depending on the study 4,5 .…”
Section: Introductionmentioning
confidence: 99%